Persepsi Guru SD/MI Tentang Pendidikan Seks Bagi Anak di Era Revolusi 4.0 - Hana Lestari; Jonari Hanafi (Reslaj : Religion Education Social Laa Roiba Journal, 2020)
ABSTRACT Teachers' perceptions of sex education are key points in developing an appropriate sex education model for children to prevent sexual abuse. This study aims to determine teachers' perceptions about sex education, sexual harassment, and prevention of sexual harassment in the revolutionary era 4.0. The study was conducted in 5 SDNs and 5 MIs in Bogor Regency and obtained 124 teachers as respondents who were taken randomly. This research uses a descriptive qualitative approach. The results of this study are (1) In the era of the industrial revolution 4.0, an understanding of sex education for children is needed as one of cultivating character in children so that they can be responsible for themselves and protect and avoid themselves from sexual violence. However, teachers 'perceptions of sex education are still taboo to discuss, so that teachers' understanding is limited by focusing on the boundaries of the relationship between men and women, and information related to sexual education that is conveyed to students is not systematic, situational in nature, not evenly distributed to all students; (2) teachers' perceptions of sexual harassment in the form of physical violence, psychological violence and unpleasant sexual violence against children; (3) teachers' perceptions in preventing sexual harassment by deepening children's religious values, recognizing physical or behavioral differences between boys and girls, recognizing children's family members, fostering student's courage, teaching the limits of genitalia, then teaching boundaries association of children. Keyword: Elementary school, Sex Education For Children, Teachers’ Perseptions